ANALISIS PENGENDALIAN KUALITAS PRODUK KANTONG SEMEN PADA LINE IV PABRIK KANTONG PT SEMEN PADANG - Tri Ernita (Sekolah Tinggi Teknologi Industri Padang, 2016)
PT Semen Padang is the oldest cement factory in Indonesia was established on March 18, 1910. Semen Padang is located in the Village District of Lubuk Kilangan Indarung Madya city of Padang, approximately 15 km from the center of Padang West Sumatra at an altitude of 350 above sea level. PT Semen Padang not only produce high quality cement, but also manufacture cement bags which will facilitate the distribution of cement. Bags of cement were produced under the Ministry of Transportation Distribution and PT Semen Padang or Bureau bag factory located at Km 2 By Pass street, Padang. Bureau bag factory produces 40 Kg bag with size and the size of 50 kg. Based on the results of the overall discussion on the control of product quality cement bags known that quality control is implemented is still not optimal. Paretto diagram of the processing, there are six causes of disability among other cement bags 1. Defects in the logo, 2. Glue the tube body portion is not flat, 3. Tube not cut / no separate, 4. Installation of the valve / valve is not appropriate, 5. Glue at the top and bottom of the bag uneven, and 6. Fold the top and bottom are not perfect. The most dominant defect occurs during the production process on line IV, namely, fold the top and bottom of the bag is not perfect for 26 280 of the 77 295 total defective products, defective bags or 34% of the total number of defective products and improper valve installation for 23 575 of the 77 295 total products disability, which has a defect rate of 30.5% of the existing number of defective products. Selanjutya based on analysis of a causal diagram is known that factors that cause many machining equipment occurred a defective product, so it needs to be evaluated again on machinery and equipment so as to reduce or eliminate defects that may occur. Then on analysis using p control map for the entire product defects that occur in the production process shows that not all the data are within the control limits. Keywords: Cause and Effect Diagram, Cement Bags, Control Charts P, Defective Products, Pareto Diagram, Quality Control.